HISTOMORPHOMETRY OF SMALL INTESTINE OF BALI DUCKS AT DIFFERENT AGES - Maria Nindi Dewi Sugiarto; Ni Luh Eka Setiasih; Luh Gde Sri Surya Heryani; I Ketut Suatha; Ni Nyoman Werdi Susari; I Gede Soma (Buletin Veteriner Udayana, 2024)
Bali ducks are one of the local poultry breeds that have high potential as producers of meat and eggs. The existence of this Balinese duck is spread evenly in rural areas in Bali. This study aims to histomorphometry of the small intestine of Bali ducks at different ages. In this study, 18 male Bali ducks were used as small intestine samples at 1 month, 3 months and 5 months. Bali ducks were obtained from a duck farm in Mengwi District, Badung Regency, Bali Province. Sampling of the small intestine was carried out in three parts, namely the duodenum, jejunum and ileum, then the organs were fixed with NBF 10% which was then made into histological preparations with HE staining. The research results are presented in a quantitative descriptive form. The results showed that the histological structure of the small intestine, namely the duodenum, jejunum and ileum, is composed of four layers, namely the tunica mucosa, tunica submucosa, tunica muscularis and the outermost is tunica serosa. The histomorphometric results, namely the total thickness of the layers that make up the small intestine of Bali ducks aged 1, 3, and 5 months respectively were 180.39 ± 29.59µm; 170.35±32.91µm; 302.09±78.94µm. It can be concluded that the histomorphometry of the small intestine of Bali ducks in ducks aged 1, 3, and 5 months has differences of thickness.